A note on the territorial limits of the Atlantic forest - Muylaert, Renata Lara [UNESP]; Vancine, Maurício Humberto [UNESP]; Bernardo, Rodrigo [UNESP]; Oshima, Júlia Emi Faria [UNESP]; Sobral-Souza, Thadeu [UNESP]; Tonetti, Vinicius Rodrigues [UNESP]; Niebuhr, Bernardo Brandão [UNESP]; Ribeiro, Milton Cezar [UNESP] (My University, 2018)
The geographic delimitation of a biome encompasses questions that involve environmental factors such as climate and vegetation characteristics as well as political aspects. Consequently, variation on biome delimitation is recurrent. The Atlantic Forest is one of the most important biodiversity hotspots in the world, and historically several territorial delimitations have been proposed for this biome. Here we aim to 1) discuss the four main delimitations and 2) based on the existing limits, discuss their union (Integrative limit) and intersection (Consensual limit). The main limits present consensual and integrative areas of 1.01 and 1.62 million km2, respectively. Five regions of divergence must be carefully evaluated. Finally, we suggest a debate about the use of limits in ecological studies and their application in biodiversity conservation studies.
Uma nota sobre os limites territoriais da mata Atlântica
Keywords: Biodiversity hotspot; Biome; Geographic distribution; Historical biogeography; Tropical forest